The structural phases and vibrational properties of Mo1−xWxTe2 alloys. (1st September 2017) - Oliver, Sean M; Beams, Ryan; Krylyuk, Sergiy; Kalish, Irina; Singh, Arunima K; Bruma, Alina; Tavazza, Francesca; Joshi, Jaydeep; Stone, Iris R; Stranick, Stephan J; Davydov, Albert V; Vora, Patrick M
Abstract: The structural polymorphism in transition metal dichalcogenides (TMDs) provides exciting opportunities for developing advanced electronics. For example, MoTe2 crystallizes in the 2H semiconducting phase at ambient temperature and pressure, but transitions into the 1T′ semimetallic phase at high temperatures. Alloying MoTe2 with WTe2 reduces the energy barrier between these two phases, while also allowing access to the T d Weyl semimetal phase. The Mo 1 − x Wx Te2 alloy system is therefore promising for developing phase change memory technology. However, achieving this goal necessitates a detailed understanding of the phase composition in the MoTe2 -WTe2 system. We combine polarization-resolved Raman spectroscopy with x-ray diffraction (XRD) and scanning transmission electron microscopy (STEM) to study bulk Mo 1 − x Wx Te2 alloys over the full compositional range x from 0 to 1. We identify Raman and XRD signatures characteristic of the 2H, 1T′, and T d structural phases that agree with density-functional theory (DFT) calculations, and use them to identify phase fields in the MoTe2 –WTe2 system, including single-phase 2H, 1T′, and T d regions, as well as a two-phase 1T′  +  T d region. Disorder arising from compositional fluctuations in Mo 1 − x Wx Te2 alloys breaks inversion and translational symmetry, leading to the activation of an infrared 1T′-MoTe2 mode and the enhancement of a double-resonance Raman process in 2H-Mo 1 − x Wx Te2 alloys. Compositional fluctuations limit the phonon correlation length, which we estimate by fitting the observed asymmetric Raman lineshapes with a phonon confinement model. These observations reveal the important role of disorder in Mo 1 − x Wx Te2 alloys, clarify the structural phase boundaries, and provide a foundation for future explorations of phase transitions and electronic phenomena in this system.